Targeted sequencing of 36 known or putative colorectal cancer susceptibility genes. Issue 5 (23rd July 2017) - DeRycke, Melissa S.; Gunawardena, Shanaka; Balcom, Jessica R.; Pickart, Angela M.; Waltman, Lindsey A.; French, Amy J.; McDonnell, Shannon; Riska, Shaun M.; Fogarty, Zachary C.; Larson, Melissa C.; Middha, Sumit; Eckloff, Bruce W.; et al.
Abstract: Background: Mutations in several genes predispose to colorectal cancer. Genetic testing for hereditary colorectal cancer syndromes was previously limited to single gene tests; thus, only a very limited number of genes were tested, and rarely those infrequently mutated in colorectal cancer. Next‐generation sequencing technologies have made it possible to sequencing panels of genes known and suspected to influence colorectal cancer susceptibility. Methods: Targeted sequencing of 36 known or putative CRC susceptibility genes was conducted for 1231 CRC cases from five subsets: (1) Familial Colorectal Cancer Type X ( n  = 153); (2) CRC unselected by tumor immunohistochemical or microsatellite stability testing ( n  = 548); (3) young onset (age <50 years) ( n  = 333); (4) proficient mismatch repair (MMR) in cases diagnosed at ≥50 years ( n  = 68); and (5) deficient MMR CRCs with no germline mutations in MLH1, MSH2, MSH6, or PMS2 ( n  = 129). Ninety‐three unaffected controls were also sequenced. Results: Overall, 29 nonsense, 43 frame‐shift, 13 splice site, six initiator codon variants, one stop codon, 12 exonic deletions, 658 missense, and 17 indels were identified. Missense variants were reviewed by genetic counselors to determine pathogenicity; 13 were pathogenic, 61 were not pathogenic, and 584 were variants of uncertain significance. Overall, we identified 92 cases with pathogenic mutations in APC, MLH1, MSH2, MSH6, or multiple pathogenic MUTYH mutations (7.5%). Four cases with intact MMR protein expression by immunohistochemistry carried pathogenic MMR mutations. Conclusions: Results across case subsets may help prioritize genes for inclusion in clinical gene panel tests and underscore the issue of variants of uncertain significance both in well‐characterized genes and those for which limited experience has accumulated. Abstract : Thirty‐six genes known or suspected to be involved in hereditary colorectal cancer were targeted for germline sequencing in 1231 cases. We compared the type and frequency of variants in controls and five subsets of cases, including Familial Colorectal Cancer Type X, unselected cases with no tumor immunohistochemical or microsatellite stability testing, young onset (<50 years), proficient mismatch repair, and deficient mismatch repair with no germline mutations present in MLH1, MSH2, or PMS2.